2022
DOI: 10.1073/pnas.2111380119
|View full text |Cite
|
Sign up to set email alerts
|

iASPP suppresses Gp78-mediated TMCO1 degradation to maintain Ca 2+ homeostasis and control tumor growth and drug resistance

Abstract: Ca2+ release from the endoplasmic reticulum (ER) is an essential event in the modulation of Ca2+ homeostasis, which is coordinated by multiple biological processes, ranging from cell proliferation to apoptosis. Deregulated Ca2+ homeostasis is linked with various cancer hallmarks; thus, uncovering the mechanisms underlying Ca2+ homeostasis dynamics may lead to new anticancer treatment strategies. Here, we demonstrate that a reported Ca2+-channel protein TMCO1 (transmembrane and coiled-coil domains 1) is overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…5 a, b), suggesting that TMCO1 depletion may promote IRE1α protein stability at the post-transcriptional level. To determine whether TMCO1 depletion can promote IRE1α expression at the protein level, we treated WT and KD cells with cycloheximide (CHX), a widely used protein synthesis inhibitor in eukaryotic cells [ 60 ]. We found that the half-life of IRE1α protein was dramatically increased in TMCO1 KD cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 a, b), suggesting that TMCO1 depletion may promote IRE1α protein stability at the post-transcriptional level. To determine whether TMCO1 depletion can promote IRE1α expression at the protein level, we treated WT and KD cells with cycloheximide (CHX), a widely used protein synthesis inhibitor in eukaryotic cells [ 60 ]. We found that the half-life of IRE1α protein was dramatically increased in TMCO1 KD cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SERCAs have been recently shown to protect cancer stem cells (CSCs) from glucose starvation-induced apoptosis by limiting cytosolic Ca 2+ sourced from the ER [30]. We have reported that the SOICR channel protein TMCO1 promotes tumor growth and protects colon cancer cells from staurosporine-induced apoptosis, by limiting cytosolic Ca 2+ dynamics [31]. Another study reported that TMCO1 inhibits tumor growth in urinary bladder urothelial carcinoma, but whether this effect is related to its ER Ca 2+ regulatory activity remains to be determined [32].…”
Section: Disturbed Organelle Calcium Homeostasis and Cell Proliferationmentioning
confidence: 99%
“…iASPP does this by specifically stabilizing TMCO1. Mechanistically, iASPP directly binds with the ER-associated degradation E3 ligase, glycoprotein 78 (Gp78), and prevents it from binding with TMCO1, leading to a reduced Gp78-mediated TMCO1 protein degradation in colon cancers [31].…”
Section: Trends Trends In In Cell Biologymentioning
confidence: 99%
“…Through bioinformatics analysis, Professor Hu's research team found that the ER calcium channel protein TMCO1 is crucial for cells to cope with ER calcium overload and maintain calcium homeostasis. Studies found that inhibiting the expression of TMCO1 would lead to intracellular Ca 2+ imbalance, thus effectively blocking the malignant proliferation of tumor cells [ 93 ]. This study extends the scientific view that calcium homeostasis is involved in forming malignant phenotypes in tumors and provides an important target for cancer treatment strategies through calcium imbalance.…”
Section: New Approaches To Metal Ions-induced Cell Death and Their An...mentioning
confidence: 99%